2017
DOI: 10.1007/s12282-017-0763-2
|View full text |Cite
|
Sign up to set email alerts
|

Digital volumetric measurement of mammographic density and the risk of overlooking cancer in Japanese women

Abstract: The proportions of Japanese women with dense breasts were high. In addition, the false-negative rate for women with dense breasts was also high. Owing to this, Japanese women with dense breasts may need to commonly undergo additional tests to ensure detection of breast cancer in the screening MMG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 21 publications
1
10
1
Order By: Relevance
“…The study showed AW were more likely to have low MBD (65%), whereas high MBD was seen in the majority of JWJ (90%). The high MBD result among JWJ was consistent with findings by Sawada (2017) (Sawada, 2017). Odds ratios provided further evidence of differing MBD between ethnicities.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The study showed AW were more likely to have low MBD (65%), whereas high MBD was seen in the majority of JWJ (90%). The high MBD result among JWJ was consistent with findings by Sawada (2017) (Sawada, 2017). Odds ratios provided further evidence of differing MBD between ethnicities.…”
Section: Discussionsupporting
confidence: 89%
“…Women living in Australia who were born in countries with predominantly Asian ancestry had high MBD (Bell et al, 2019). In Japan, high MBD was observed in 78% of non-symptomatic women and 87% of breast cancer patients using a quantitative MBD measurement (Sawada, 2017). A study comparing the MBD of Japanese women in Hawaii and Japan reported that the former had significantly higher percent densities than the latter (Maskarinec et al, 2002).…”
Section: Research Articlementioning
confidence: 99%
“…Indeed, the rate of dense breasts in our study was relatively higher than the rate found in previous Western studies about imaging features of high-risk women [3, 20]. Sawada et al [26] also reported that the false-negative rate for Japanese women with dense breasts was high. For our current study, in all the cases where mammography was unable to detect the lesions, the breast density was described as either heterogeneous or extreme density.…”
Section: Discussioncontrasting
confidence: 71%
“…The strong tendency of high-risk groups to have dense breast tissue is known [25]. The rate of Japanese women with dense breasts is especially higher than Western people [2628]. In addition, it has been suggested that breast density is associated with the risk of breast cancer [29, 30].…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer is one of the most common female tumors, and is a leading cause of female mortality worldwide. The incidence of breast cancer is on the increase annually with a trend towards the younger population (1,2). With the continuous development of medical technology, research on the pathogenesis of breast cancer has revealed abundant information that was previously unknown.…”
Section: Introductionmentioning
confidence: 99%